1999
DOI: 10.1103/physrevlett.82.4918
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting GapΔc, the PseudogapΔp, and

Abstract: The superconducting gap ∆ c , the pseudogap ∆ p and pair fluctuations above T c in overdoped Y 1−x Ca x Ba 2 Cu 3 O 7−δ from femtosecond time-domain spectroscopy. The low-energy electronic excitation spectrum and gap structure in optimally doped and overdoped Y1−xCaxBa2Cu3O 7−δ single crystals are investigated by real-time measurements of the quasiparticle relaxation dynamics with femtosecond optical spectroscopy. From the amplitude of the photoinduced reflectivity as a function of time, temperature and doping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

31
271
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(303 citation statements)
references
References 18 publications
31
271
0
1
Order By: Relevance
“…As T c is approached from below, τ R shows a divergence [see inset to Fig. 2 b)] as observed already in YBCO, Tl-2223 [3,6] and also in NCCO [5]. This is, through the relation τ R ∝ 1/∆(T), associated with the closure of the isotropic collective mean-field-like gap [1].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…As T c is approached from below, τ R shows a divergence [see inset to Fig. 2 b)] as observed already in YBCO, Tl-2223 [3,6] and also in NCCO [5]. This is, through the relation τ R ∝ 1/∆(T), associated with the closure of the isotropic collective mean-field-like gap [1].…”
mentioning
confidence: 95%
“…In YBCO two distinct relaxation components below T c (one present also above T c with T-independent τ, and the other with divergent τ R at T c [3,6]) suggest the co-existing presence of two distinct energy gaps: a T-independent pseudogap ∆ p and a mean-field-like T-dependent gap ∆ c (T) [3]. Two distinct relaxation components with opposite signs were observed also on BiSCO-2212 and Tl-2201 [4], suggesting that the two component behavior is quite general in high-T c superconductors near optimal doping.…”
mentioning
confidence: 99%
“…The term pseudogap has been coined to describe this kind of physics. The presence of pseudogap has been established through the measurements of the nuclear magnetic resonance (NMR) [5], the scanning tunneling spectroscopy [6][7][8][9], the analysis of the electronic Raman scattering [10][11][12], through time-resolved optical spectroscopy [13][14][15][16][17][18], and through the ARPES [19][20][21][22][23][24][25]. The observed strong Nernst effect in cuprates has been also attributed to it [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Although the interaction of electrons with lattice vibrations is not likely to solely account for the essential properties of high-T c superconductors (HTSCs), many probes including angle-resolved photoemission, [1][2][3][4][5] inelastic neutron scattering, 6 , tunneling 7,8 and Raman 9 spectroscopies have revealed that electron-phonon interactions have significant effects on various properties. Complementary to the timeintegrated techniques, different ultrafast pump-probe techniques [10][11][12][13][14][15] have been used to disentangle microscopic interactions in HTSCs. These techniques aim to study the recombination of photoexcited quasiparticles and the resulting recovery of the superconducting condensate.…”
Section: Introductionmentioning
confidence: 99%